Virgin whore - Solberg, Emma Maggie (Cornell University Press, 2018)
"In Virgin Whore, Emma Maggie Solberg uncovers a surprisingly prevalent theme in late English medieval literature and culture: the celebration of the Virgin Mary's sexuality. Although history is narrated as a progressive loss of innocence, the Madonna has grown purer with each passing century. Looking to a period before the idea of her purity and virginity had ossified, Solberg uncovers depictions and interpretations of Mary, discernible in jokes and insults, icons and rituals, prayers and revelations, allegories and typologies--and in late medieval vernacular biblical drama ... By revealing the presence of this promiscuous Virgin in early English drama and late medieval literature and culture--in dirty jokes told by Boccaccio and Chaucer, Malory's Arthurian romances, and the double entendres of the allegorical Mystic Hunt of the Unicorn--Solberg provides a new understanding of Marian traditions"--